SISTEM MONITORING PENGGUNAAN DAYA LISTRIK BERBASIS INTERNET OF THINGS PADA RUMAH DENGAN MENGGUNAKAN APLIKASI BLYNK - Pela, Maria Febrianti; Pramudita, Rully (Infotech: Journal of Technology Information, 2021)
All work and human needs are highly dependent on the presence of electrical energy, especially on household needs. Human negligence in using electrical energy will cause waste in the use of electrical energy which causes soaring payments among households. This study aims to examine the application of monitoring the electrical power used in the connection of these devices remotely via the internet. The system can be implemented using NodeMCU ESP8266, PZEM-004T sensor, Liquid Crystall I2C, and the Blynk application as a user interface system on a smartphone. To be able to monitor through the Blynk application, the user must be connected to the internet and the microcontroller must be connected to the internet network. This system using the internet network will make it easier to monitor electrical power in electronic devices at home every day. The results of this study are the prototype of the electrical power monitoring system using the Blynk application can help and facilitate homeowners in monitoring electrical power when the homeowner is not at home.